Untargeted Metabolomics Study of Three Matrices: Seminal Fluid, Urine, and Serum to Search the Potential Indicators of Prostate Cancer - Buszewska-Forajta, Magdalena; Raczak-Gutknecht, Joanna; Struck-Lewicka, Wiktoria; Nizioł, Magdalena; Artymowicz, Małgorzata; Markuszewski, Marcin; Kordalewska, Marta; Matuszewski, Marcin; Markuszewski, Michał J. (Frontiers in Molecular Biosciences, 2022)
The simultaneous determination of metabolites from biological fluids may provide more accurate information about the current body condition. So far, metabolomics approach has been successfully applied to study the mechanism of several disorders and to search of novel biomarkers. Urine and plasma are widely accepted matrices for evaluation of several pathologies, while prostate cancer development is still unknown. For this reason alternative matrix, the seminal fluid was proposed to expand the knowledge about the prostate cancer pathomechanism. The main aim of this study was to develop and optimize sample preparation protocol to ensure the highest coverage of metabolome of ejaculate samples. Parameters like the type and composition of solvent mixture, time of extraction and applied volume of solvent were tested. The optimized method was applied for untargeted metabolomics profiling of seminal fluid samples obtained from CaP patients. Moreover, urine and serum samples were also prepared for untargeted metabolomics analysis. Analyses were carried out with the use of two complementary analytical techniques, GC-EI-QqQ/MS and LC-ESI-TOF/MS. Finally, the metabolic signature of seminal fluid (n=7), urine (n=7) and plasma (n=7) samples were compared. Furthermore, the hypothesis of the increased level of metabolites in ejaculate samples related to the CaP development was evaluated. The results indicated that developed and optimized sample preparation protocol for seminal fluid may be successfully applied for metabolomic study. Untargeted analysis of ejaculate enabled to determine the following classes of compounds: fatty acids, sphingolipids, phospholipids, sugars and their derivatives as well as amino acids. Finally, comparison of three tested matrices was carried out. Up to our best knowledge it is the first time, when metabolic profile of three matrices like urine, plasma and seminal fluid was compared. Based on the results, it can be pointed out that ejaculate comprises metabolic signature of both matrices (polar compounds characteristic for urine and non-polar ones present in plasma samples). Comparing to plasma, semen samples revealed to have a similar profile, however determined levels of metabolites were lower in case of ejaculate. In case of urine samples compared to semen metabolic profiles, the levels of detected metabolites were decreased in the latter ones.